Mentalist vs behaviorist: Chomsky`s linguistic theory - Yaacob, Solehah@Nik Najah Fadilah (Pusat Kembangan Kolej Universiti Islam Sultan Azlan Shah, 2016)
The research emphasizes the relationship between linguistics and logic according modern views and approaches. However, linguistic argumentation is needed for analyzing a language system that uses the meaning of expressions in a sentence to provide the complete meaning of the sentence, as there lies a dependence between expressions. In fact, the connection between expressions enhances the overall meaning from the fundamentals of the sentence structure in the logical relationship between ideas; where there lies a relation between words and thought, which is dependent on the logic of combined utterances. In order to signify the above concept of thinking, the researcher has reviewed the theory of the early system of Arabic grammar that focuses more on an analogical approach rather than anomaly. The analogical approach in the system is based on the underlying theory that implies the aforementioned relationship, even though some modern views may disagree on the interpretation of this issue.To add to the discussion, the researcher has included similar existing theories on Chomsky`s approaches, which have shown the logical approach as a result from the connection between linguistic argumentation and logic. As a result of this discussion, the connection between words and logic is shown to be a universal concept.